Espaços que suscitam sonhos: narrativas de memórias e identidades no Museu Comunitário Vivo Olho do Tempo - Tolentino, Átila Bezerra (2016)
Based on theoretical assumptions that consider the social aspects of memory, this work aims to analyze the process of construction of memories and identities of Vale do Gramame, rural area of João Pessoa, represented in the exhibition narrative of Museu Comunitário Vivo Olho do Tempo. The theoretical debate permeates study authors that consider memory as a social phenomena and consequently take into account the social aspects of identity construction. It also involves discussions by authors who treat the cultural heritage as a category of thought and his reflections on the conflicts inherent in the process of constitution of collective memories, full of disputes between remembering and forgetting and, consequently, between power and resistance. To situate the impact of creating the Museu Comunitário Vivo Olho do Tempo, it’s presented a brief historical background, conceptual and politic on the field of social museology and Sociomuseology. The intention is to identifying how the reflections and debates in the area influenced the design and the implementation of public policies for the field of museums today and the establishment of various community-based museums in Brazil. Moreover, this work attempts to challenge the interfaces and differences between which is considered social museology and Sociomuseology, as well as the dilemmas and conflicts in the academic field which govern this reflection line. As the museum's keynote is to present the cultural references and Vale do Gramame memories, which thus constitute its identity, from the look of the masters of local popular culture, this work also seeks to give voice to those social actors. From interviews, their voices and their memories are brought to light, in order to evoke the senses and meanings that these social subjects give to their role as socio-historical actors of the construction of their identities and their cultural references.